Electric field induced structural changes in alpha-SiO2 and AlPO4 - M, J.Davaasambuu, B.Burmaa; U.Pietch (Scientific transaction of the National University of Mongolia. Physics, 2022)
Electric field induced structural changes in alpha-SiO2 and AlPO4